Tributação indutora e tutela do meio ambiente: Análise sob o prisma da função promocional do direito. - Souza Júnior, Renovato Ferreira de (2015)
This study aims to analyze the role of inducing taxation as environmental defense instrument from the perspective of the promotional function of law and constitutional principles of tax. The Federal Constitution of 1988 expressly provides for the right to an ecologically balanced environment, and the principle of Economic Order to protect the environment including through differential treatment as the environmental impact. While the worsening environmental crisis and the need for equalization between economic development and the protection of the environment, taxes come just as state intervention instruments aimed at influencing the behavior of economic agents, inducing interventions directed to the rational use of natural resources and sustainability, and discouraging those other degrading. Examines, therefore, its main theoretical aspects and criteria for characterization of environmental taxation. The end result of the research points mainly to the need to search combination of various tax mechanisms with environmental extrafiscal purpose, in order to leverage the use of the tax as environmental protection instrument.